2020
DOI: 10.1155/2020/4085349
|View full text |Cite
|
Sign up to set email alerts
|

Real-Life Diagnostic Accuracy of MRI in Prenatal Diagnosis

Abstract: There is some controversy about the value of fetal MRI in prenatal diagnosis, and most of the studies examine its accuracy in central nervous system (CNS) pathology. The objective of this retrospective study was to assess the diagnostic accuracy and usefulness of fetal MRI in the prenatal diagnosis of central nervous system (CNS) pathology and non-CNS pathology. Patients referred to the Radiology Department between 2007 and 2018 for a fetal MRI after detection of an anomaly in the fetal ultrasound, a high-risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 27 publications
5
8
0
Order By: Relevance
“…In agreement to our study, Recio Rodríguez et al, (12) study reported that the diagnostic accuracy of the fetal MRI was higher than that of fetal ultrasound in all cases and all indications. The differences in diagnostic accuracy between fetal ultrasound and fetal MRI were significant for all cases (90.4% vs 97%; p<0.001).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…In agreement to our study, Recio Rodríguez et al, (12) study reported that the diagnostic accuracy of the fetal MRI was higher than that of fetal ultrasound in all cases and all indications. The differences in diagnostic accuracy between fetal ultrasound and fetal MRI were significant for all cases (90.4% vs 97%; p<0.001).…”
Section: Resultssupporting
confidence: 93%
“…The differences in diagnostic accuracy between fetal ultrasound and fetal MRI were significant for all cases (90.4% vs 97%; p<0.001). In addition Our results agreed with those obtained by Recio Rodríguez et al, (12) study which showed that the diagnostic accuracy of the fetal MRI was higher than that of fetal ultrasound and the differences in diagnostic accuracy between fetal ultrasound and fetal MRI were significant for CNS pathology (89.7% vs 98.1%; p<0.001) while fetal ultrasound and fetal MRI were concordant in 90.2% of the cases.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…11 The incorporation of MRI has enhanced the precision of central nervous system (CNS) diagnoses 6 and in a specific study, it was estimated to have provided additional information in 23% of investigated cases with CNS malformations. 20 With increased diagnostic precision, there is a probability of detecting a greater number of fetuses with abnormal findings of uncertain significance. However, to the best of our knowledge, the effect of introducing these advanced diagnostic tools on TOPFA rates has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Pregnant women meeting one or more of the following conditions should be considered as a high-risk pregnancy: a previous child with chromosomal abnormalities or other congenital defects, mother or father with a chromosomal abnormality, suffering from an X-linked disease, having a chronic disease such as diabetes or certain endocrine disorders, having a family history of malformations, chromosomal abnormalities or congenital metabolic disorders, suffering from an infection during pregnancy, twin pregnancy, maternal obesity, advanced maternal age (>35 years old), consuming drugs during pregnancy, being exposed to radiation or toxic products for work-related or temporary reasons, assisted reproductive techniques. The possibility of a pregnant woman with one or more of these conditions or having a fetus with a congenital defect is multiplied by a greater or lesser factor that depends on the altered condition detected [ 1 , 4 , 5 , 6 ]. Additionally, suffering from a mental health issue during the perinatal period (i.e., stress, anxiety, depression, psychopathological symptoms, post-traumatic stress disorder) is a risk factor that can have a negative impact on the maternal health and the offspring [ 7 ].…”
mentioning
confidence: 99%